Inventarisasi Tanaman Obat untuk Penderita Penyakit Tidak Menular di Kota Makassar - Asni Amin; Faradiba Faradiba (Makassar Natural Product Journal (MNPJ), 2023)
Makassar City is one of the largest cities in the eastern region of Indonesia with the lifestyle of its society having undergone changes, starting from consuming instant food, lack of movement, and rarely exercising. So that, there is an increase in non-infectious diseases. People in the city of Makassar use traditional medicinal plants in accordance with the changing trend of people who return to nature "back to the nature". Yhe purpose of this study, we wanted to find out how the use and the process and the application of traditional medicine regarding its types, morphology, and its properties in Makassar society. Furthermore, as well as to get the suitability of scientific data by community use. The research method used was a descriptive survey with a qualitative approach, a combination method of purposive sampling and snowball sampling was used in determining the sample, the data was collected by direct observation and in-depth interviews. The results of research that have been carried out obtained about 47 types of plants, the part of the plant that used often by the community is leaves. And there are also the rhizomes, bark, fruit skin, stems, fruit, tubers, seeds, and herbs. Moreover, the processing of traditional medicine was boiled, brewed, pounded, squeezed, and without processing, while the application of use is by drinking, rubbing on the affected area, smearing, patching, and consume immediately. Based on data from various literature, some medicinal plants that have been used by society have scientific evidence as to their activities. The people of Makassar city use traditional medicinal plants in the treatment of non-infectious diseases and also there is scientific evidence on some plants that supports the use of traditional medicines by society.